Electronic and optical properties of α‐MoO3/TiO2 heterostructures: A DFT study. Issue 18 (31st July 2018) - Meng, Qiangqiang; Fan, Lele; Zhu, Lei; Xu, Ning; Zhang, Qinfang
Abstract: The coupling of metal oxide semiconductors has become an effective method to improve the separation of photon‐generated carriers and light absorption efficiency. In this study, we explored electronic and optical properties of monolayer and bilayer α‐MoO3 on TiO2 (001) surface. It is observed that α‐MoO3 /TiO2 heterostructures can form a stable Mo‐O‐Ti bonding mode at the interface. Electrons transfer from TiO2 (001) surface to the α‐MoO3, leading to the enhancement of the valence band and the optical absorption spectrum in visible light region. In addition, this proper charge transfer generates a built‐in electric field between the interface regions of bilayer α‐MoO3 /TiO2 heterostructure and forms a favorable type‐II band alignment between the two α‐MoO3 layers. The α‐MoO3 /TiO2 heterostructure can prevent the recombination of the electron‐hole pairs; thus, excite electrons can easily move from TiO2 to the inner layer, and then to the outer layer of α‐MoO3 . These results demonstrate that the bilayer α‐MoO3 /TiO2 heterostructure, especially the outer layer α‐MoO3, has efficient photoelectric performance. Abstract : α‐MoO3 /TiO2 heterostructure can form a stable Mo‐O‐Ti bonding mode at the interface. In particular, a favorable type‐II band alignment is formed between the two α‐MoO3 layers of bilayer α‐MoO3 /TiO2 heterostructure, which can prevent the recombination of the electron‐hole pairs. Thus, excited electrons can easily move from TiO2 to the inner layer, and then to the outer layer of α‐MoO3 .